Petrography, geochemistry and detrital zircon geochronology of the Srisailam Quartzite Formation, Cuddapah Basin, India: Implications for depositional age, correlation and provenance - Mukherjee, Sneha; Das, Paramita; Ghosh, Gautam; Bose, Sankar; Amal Dev, J.; Das, Kaushik; Tomson, J.K. (Precambrian research, 2023)
[Display omitted] •Duration of sedimentation in the Srisailam sub-basin was > 1840 Ma ≤ 1770 Ma.•The Srisailam Formation formed in a passive margin setting.•The dominant source area for the Srisailam Formation was the Dharwar Craton.•The Srisailam Formation contains Palaeo-Mesoarchaean and traces of Haedean zircons.•The Srisailam Formation is correlated with the Pulivendla Formation, Chitravati Group. The Mesoproterozoic Cuddapah Basin consists of four unconformity-bound sequences, i.e., Papaghni Group, Chitravati Group, Srisailam Formation and Kurnool Group. A fair amount of geochronological and geochemical data is available from the basal Papaghni Group and Chitravati Group as well as the overthrusted Nallamalai Group. Due to limited geochronological and geochemical constraints, the Srisailam Formation, however, remains a subject of speculation regarding the time of sediment deposition, sediment source locations, and tectonic setting. In this work, we present new geochronological and geochemical data (zircon U-Pb) from samples of the Srisailam Formation. The new data suggest that the Srisailam Formation correlates temporally with the basal Chitravati Group and is largely disparate from the allochthonous Nallamalai Group. The sediments of the Srisailam Formation contain a minor yet significant number of Palaeo-Mesoarchaean detrital zircon with traces of Haedean zircon. Based on our detrital zircon data, we argue that the sedimentation in the Srisailam sub-basin initiated after ca. 1840 Ma and continued till ≤ ca. 1770 Ma and the sediments were mainly sourced from Neoarchaean to Paleoproterozoic terrains including the Dharwar Craton, and sedimentation was initiated in a rift basin that subsequently evolved to a passive margin setting.